1985
DOI: 10.1007/bf00252716
|View full text |Cite
|
Sign up to set email alerts
|

Radionuclide absolute left ventricular volumes during upright exercise: validation in normal subjects by simultaneous hemodynamic measurements

Abstract: A nongeometric radionuclide technique for the determination of absolute left ventricular volumes was validated during exercise in nine normal subjects. Simultaneous reference stroke volume and cardiac output measurements were obtained by the Fick method. The reference left ventricular volumes were calculated by combining the Fick stroke volume and the isotopic ejection fraction. Data were collected at rest in the supine and upright positions and during 60 degrees upright exercise, at three levels of increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
1999
1999

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Most of the previous reports dealing with the determination of changes in LV volumes in response to exercise, using radionuclide count-based method and peripheral blood sampling have often ignored the possible effects of exercise or intervention on blood activity (1,4,8,25,26). On the other hand, some investigators have taken into account the changes in blood activity during time and exercise (13,17,30,40), whereas others have found that blood activity does not change with exercise (28,36).…”
Section: Nuklearmedizin 1997; 36: 259-64mentioning
confidence: 99%
“…Most of the previous reports dealing with the determination of changes in LV volumes in response to exercise, using radionuclide count-based method and peripheral blood sampling have often ignored the possible effects of exercise or intervention on blood activity (1,4,8,25,26). On the other hand, some investigators have taken into account the changes in blood activity during time and exercise (13,17,30,40), whereas others have found that blood activity does not change with exercise (28,36).…”
Section: Nuklearmedizin 1997; 36: 259-64mentioning
confidence: 99%